Unsupervised machine learning of topological phase transitions from experimental data. Issue 3 (14th July 2021) - Käming, Niklas; Dawid, Anna; Kottmann, Korbinian; Lewenstein, Maciej; Sengstock, Klaus; Dauphin, Alexandre; Weitenberg, Christof
Abstract: Identifying phase transitions is one of the key challenges in quantum many-body physics. Recently, machine learning methods have been shown to be an alternative way of localising phase boundaries from noisy and imperfect data without the knowledge of the order parameter. Here, we apply different unsupervised machine learning techniques, including anomaly detection and influence functions, to experimental data from ultracold atoms. In this way, we obtain the topological phase diagram of the Haldane model in a completely unbiased fashion. We show that these methods can successfully be applied to experimental data at finite temperatures and to the data of Floquet systems when post-processing the data to a single micromotion phase. Our work provides a benchmark for the unsupervised detection of new exotic phases in complex many-body systems.